2005
DOI: 10.1148/radiol.2353040593
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Dysfunction and Pulmonary Obstruction Index at Helical CT: Prediction of Clinical Outcome during 3-month Follow-up in Patients with Acute Pulmonary Embolism

Abstract: Markers of RVD and pulmonary vascular obstruction, assessed with helical CT at baseline, help predict mortality during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
300
8
21

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 464 publications
(361 citation statements)
references
References 19 publications
32
300
8
21
Order By: Relevance
“…Several previous studies have suggested that pulmonary arterial embolic burden assessed by CT as well as by RV/LV ratio is also a predictor for APTE patients (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). On the other hand, Ghaye et al (19) suggested that RV/LV diameter ratio and azygos vein diameter were significant predictors, and that pulmonary arterial embolic burden was not.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Several previous studies have suggested that pulmonary arterial embolic burden assessed by CT as well as by RV/LV ratio is also a predictor for APTE patients (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). On the other hand, Ghaye et al (19) suggested that RV/LV diameter ratio and azygos vein diameter were significant predictors, and that pulmonary arterial embolic burden was not.…”
Section: Discussionmentioning
confidence: 98%
“…According to the past literatures (14)(15)(16)(17)(18)(19)(20), the scans were evaluated by measuring the minor axes of the right and left ventricles of the heart in the transverse plane at their widest points between the inner surface of the free wall and the surface of the interventricular septum. These maximum dimensions may be found at different levels.…”
Section: Contrast-enhanced Ctmentioning
confidence: 99%
See 3 more Smart Citations